User satisfaction of Museum Pendidikan Nasional website: An EUCS & DeLone McLean approach - Tessar Permata, Alvin; Hadiapurwa, Angga; Yanti Ramadhan, Suci (Record and Library Journal, 2025)
Background of the study: User satisfaction is crucial for evaluating website design, especially for cultural and educational institutions such as museums. Purpose: The purpose of this study is to measure how the five dimensions of content, accuracy, format, ease of use, and timeliness affect user satisfaction. Method: A quantitative approach was used, employing the EUCS model and the DeLone and McLean Framework, through a survey of 224 students from the Faculty of Education at Universitas Pendidikan Indonesia. Data were collected through a structured questionnaire and analyzed using multiple linear regression. Findings: The findings of this study indicate that content, accuracy, and format are the most significant factors influencing user satisfaction, explaining nearly 93% of the variation in satisfaction. However, ease of use and timeliness show weaker effects. Conclusion: This study suggests that museum websites should prioritize content quality and accuracy while maintaining a user-friendly design. Additionally, further research with a larger, more diverse sample and longitudinal studies is recommended to examine changes in satisfaction over time.